Alchemy Field Report on FCC Micro Credit Programs to Refugees in Mozambique - Omata, Naohiko (Tufts Archival Research Center, 2005)
This paper is a report by an Alchemy intern at Fundo de Credito Communtario (FCC) in Mozambique for the summer of 2004. The report consists of five sections. The first section briefly outlines the current environment surrounding refugees in Mozambique and the refugee policy of Mozambican government. The next section explains micro credit lending program of FCC in Mozambique, with emphasis on its Refugee Integration Program (RIP), as well as FCCâs lending stance in its program. In the third section, the paper evaluates the impact of FCCâs micro credit lending program in Maputo based on the latest results of Alchemy interviews with FCC RIP clients and non-clients. Then, it presents recommendation and proposals for FCC and concludes with prospective direction of FCC.